Queering Asylum Anxieties: Sexual Orientation and Gender Identity Refugee Claims - Raj, Senthorun (feminists@law, 2017)
Over the last three decades, an increasing number of Anglophone courts have recognised asylum claims on the basis of sexual orientation and gender identity. Such jurisprudence has been heralded for “progressing” LGBTI rights. Yet, the progressive promise of these “pro-LGBTI” decisions leaves much more to be desired. Often formulated under the rubric of a “particular social group,” the extent to which queer refugees have been granted protection has been contingent on whether they subscribe to normative ideas of intimacy, identity, and injury. Specifically, queer refugees must demonstrate they have a “well-founded fear of persecution” by subscribing to ethnocentric assumptions about sexual citizenship, gender expression, erotic relationships, and state violence. While the concept of fear has been central to the grant of asylum under international law, it has also been mobilised in legal, political, and academic responses to the adjudication of such claims. Specifically, the fear about having a refugee jurisprudence that is too queer has led to states attempting to curb opening the proverbial “floodgates.” This anxious attempt at control has been painfully fleshed out in the way courts navigate the nexus between “authenticating” immutable sexual or gender identities and “counting” what amounts to sustained state persecution. Drawing on appellate case law from Australia, UK, US, and the EU, this paper disturbs how fear stifles the recognition of queer identity, intimacy, and injury. By disrupting judicial gestures, it considers how “asylum anxieties” continue to undermine queer claims for protection.